IMPROVEMENT OF INFRASTRUCTURE ON THE OUTSKIRTS OF HIGHWAYS: ENHANCING SAFETY, ECONOMIC DEVELOPMENT, AND SUSTAINABILITY (Proceedings of Scientific Conference on Multidisciplinary Studies, 2024)
Highways are critical to modern economies, facilitating the efficient movement of goods, services, and people over vast distances. However, while significant attention is often given to the design and maintenance of the highways themselves, the infrastructure on their outskirts—where highways intersect with local communities and other transportation networks—often receives less focus. These outskirts serve as crucial transition zones, linking high-speed transportation corridors with urban, suburban, and rural areas, thereby playing a pivotal role in ensuring safety, travel efficiency, and regional economic vitality. In many regions, the outskirts of highways suffer from infrastructure deficiencies, such as poorly maintained roads, inadequate signage, and a lack of service facilities, leading to increased accident rates, economic stagnation, and environmental degradation. Additionally, the absence of well-planned service areas and economic development zones can result in missed opportunities for growth. This study addresses these concerns by analyzing the current state of infrastructure on the outskirts of highways, identifying key challenges, and proposing solutions focused on safety, economic development, and sustainability. The research combines quantitative data analysis and qualitative insights from stakeholders to provide a holistic view of the benefits of targeted infrastructure improvements. The findings aim to inform policymakers, urban planners, and other stakeholders involved in highway infrastructure development, with the goal of transforming highway outskirts into spaces that enhance transportation experiences, stimulate local economies, and promote well-being.